Knowledge of education and common activity. Building fields of education from pedagogy : Knowledge of education and common activity. Building fields of education from pedagogy - TOURIÑÁN LÓPEZ, José (Utopía y Praxis Latinoamericana, 2021)
Knowledge of education makes it possible to build fields of education over cultural areas, transforming information into knowledge and knowledge into education. We have to educate “with” the cultural area and this requires adjusting to the meaning of educating and executing pedagogical function with competence, establishing an educational relationship in which knowledge of education and common activity are necessary means. It is impossible to educate without common activity and through the educational relationship we work on the concordance between educational values and feelings to make the effective transition from knowledge to action in every built education field.